Reduction Dynamics of Doped Ceria, Nickel Oxide, and Cermet Composites Probed Using In Situ Raman Spectroscopy - Maher,RC; Shearing,PR; Brightman,E; Brett,DJL; Brandon,NP; Cohen,LF (Advanced Science, 2016)
The redox properties of gadolinium doped ceria (CGO) and nickel oxide (NiO) composite cermets underpin the operation of solid oxide electrochemical cells. Although these systems have been widely studied, a full comprehension of the reaction dynamics at the interface of these materials is lacking. Here, in situ Raman spectroscopic monitoring of the redox cycle is used to investigate the interplay between the dynamic and competing processes of hydrogen spillover and water dissociation on the doped ceria surface. In order to elucidate these mechanisms, the redox process in pure CGO and NiO is studied when exposed to wet and dry hydrogen and is compared to the cermet behavior. In dry hydrogen, CGO reduces relatively rapidly via a series of intermediate phases, while NiO reduces via a single-step process. In wet reducing atmospheres, however, the oxidation state of pure CGO is initially stabilized due to the dissociation of water by reduced Ce(III) and subsequent incorporation of oxygen into the structure. In the reduction process involving the composite cermet, the close proximity of the NiO improves the efficiency and speed of the composite reduction process. Although NiO is already incorporated into working cells, these observations suggest direct routes to further improve cell performance.